Root Exudates: Mechanistic Insight of Plant Growth Promoting Rhizobacteria for Sustainable Crop Production - Upadhyay, Sudhir K.; Srivastava, Abhishek K.; Rajput, Vishnu D.; Chauhan, Prabhat K.; Bhojiya, Ali Asger; Jain, Devendra; Chaubey, Gyaneshwer; Dwivedi, Padmanabh; Sharma, Bechan; Minkina, Tatiana (Frontiers in Microbiology, 2022)
The breaking silence between the plant roots and microorganisms in the rhizosphere, affects plant growth and physiology by impacting biochemical, molecular, nutritional, and edaphic factors. The components of the root exudates associated to microbial population, notably plant growth-promoting rhizobacteria (PGPR). The information accessible to date demonstrates that PGPR are specific to the plant's roots. However, inadequate information is accessible for developing bio-inoculation/bio-fertilizers for the crop in concern, with satisfactory results at the field level. There is a need to explore perfect candidate PGPR to meet the need for plant growth and yield. The functions of PGPR and their chemotaxis mobility towards the plant root are triggered by the cluster of genes, induced by the components of root exudates. Some reports have indicated the benefit of root exudates in plant growth and productivity, yet a methodical examination of rhizosecretion and its consequences in phytoremediation has not been made. In the light of the afore-mentioned facts, in the present review, the mechanistic insight and recent updates on the specific PGPR recruitment to improve crop production at the field level are methodically addressed.